2017
DOI: 10.1080/17483107.2017.1357052
|View full text |Cite
|
Sign up to set email alerts
|

The influence of lower-limb prostheses technology on Paracanoeing time-trial performance

Abstract: Within the Paracanoeing discipline, it is important to ensure that appropriate control is achieved by a paddler with a disability. However, this Paralympic Games discipline has seen very little attention to date. The aims of this study were to understand the kinematic impact to a paracanoeist when not utilizing the use of a prosthetic lower-limb. A kayaker with a uni-lateral transfemoral amputation completed several 200 m maximal efforts both with and without their prosthesis. When the prosthetic limb was remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Another important aspect is the symmetry of the stroke action between right and left sides, as a symmetrical propulsion force helps maintaining a constant speed ( Bjerkefors et al, 2019;Bjerkefors et al, 2018;Ellis et al, 2017;Michael et al, 2012). The three evaluated athletes presented minimal differences in their stroke length results when comparing the right and left sides.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Another important aspect is the symmetry of the stroke action between right and left sides, as a symmetrical propulsion force helps maintaining a constant speed ( Bjerkefors et al, 2019;Bjerkefors et al, 2018;Ellis et al, 2017;Michael et al, 2012). The three evaluated athletes presented minimal differences in their stroke length results when comparing the right and left sides.…”
Section: Discussionmentioning
confidence: 98%
“…The paddling action is a motor action that requires a high level of body control, since it involves complex coordination of upper limbs, trunk, hip and lower limbs under constant interaction, with reaction forces towards different directions, resulting in a forward propulsive force (Bjerkefors et al, 2019;Bjerkefors et al, 2018;Ribeiro et al, 2022;Rosen et al, 2022). However, The variables stroke frequency, speed and stroke index have been pointed out in the literature as significant indicators of efficiency, providing practical information to configure loads and monitor the performance of athletes during water training (Bjerkefors et al, 2015(Bjerkefors et al, , 2018Ellis et al, 2017;Grigorenko et al, 2004;Norrbrink et al, 2012;Rosen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Core training has proven effective in reducing the performance gap between disabled and non-disabled athletes, so that they can compete together to promote sports inclusion. A further solution could also be given by the use of prosthetic limbs, in the case of amputees, since significant differences were found in the performance, strength and use of the footrest (Ellis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…For athletes who are lower-limb amputees, changing the seated configuration will change the body centre of mass position, and the use of prostheses may improve the leverage that the limb(s) can provide. For example, in para kayak, Ellis et al [ 43 ] found that when the prosthetic limb was removed, decrements in stroke rate, stroke speed, stroke length, and overall power output were observed. Coaches should ensure the residual limb is well supported in the boat to provide the maximum leverage for optimal propulsive strength.…”
Section: Sittingmentioning
confidence: 99%